Rock and roll rhythms in swimming - Sanders, R. (Limmat Sharks Zürich, 2007)
This paper is based on the ISBS 2007 lecture honouring Geoffrey Dyson, a pioneer in putting sports science into practice. Although the term `rhythm` is frequently used by coaches, commentators, and participants in sports, it is rarely quantified. Using examples from analysis of butterfly and front crawl swimming the lecture described how rhythms may be quantified using Fourier analysis and presented `typical` results from past and current research. In combination with kinematic and kinetic data analysis of rhythms can provide an insight into what constitutes `good rhythm` in specific sports skills. Importantly, there is potential to use knowledge of rhythms.